Physiotherapy case reports on three people with progressive supranuclear palsy - Mateus, Mariana; Castro Caldas, Alexandre (Frontiers in Aging Neuroscience, 2023)
Introduction Progressive supranuclear palsy (PSP) is a neurodegenerative brain disease that affects patient’s functionality and quality of life. Physiotherapy should be recommended at the time of diagnosis to slow the progression of disability and enhance the quality of life of these patients. Clinical presentation Here, we describe three cases of patients with PSP, outlining their motor and non-motor symptoms and examining their clinical progression with physiotherapy intervention. During the initial intervention years, a reduction in the number of falls was achieved, along with improvements in gait and balance. Conclusion Exercise and physiotherapy appear to be beneficial for patients with PSP by enhancing their functionality and quality of life. Controlling or reducing the number of falls should be the primary goal of any intervention for patients with PSP.